Healing hearts: mind-body therapy for mothers after stillbirth’s silent grief - Bar, Vered; Hermesh, Tamar; Reshef, Piki; Hermetz, Shoshy; Hertz-Palmor, Nimrod; Gothelf, Doron; Mosheva, Mariela (Frontiers in Psychiatry, 2025)
IntroductionApproximately 0.75% of pregnancies end with stillbirth, often leading to depression, anxiety, posttraumatic stress symptoms and suicidality. Knowledge regarding effective treatment options is lacking. In this retrospective cohort study we present a mind-body group therapy treatment protocol that was adapted for women and their partners who suffered stillbirth and report on its clinical effectiveness. Additionally, we identified demographic and clinical factors that were associated with clinical response.MethodsSixty-one women who coped with stillbirth were enrolled to a mind-body group therapy. Questionnaires assessing symptoms of depression, anxiety, and post-traumatic stress were administered to the women before and after the group intervention.ResultsAs expected, we found high rates of depression, state and trait anxiety and post-traumatic symptoms in our cohort before mind-body group therapy. At completion of treatment, the symptoms of depression, state anxiety, post-traumatic stress and suicidality significantly decreased. Improvement in symptoms of depression and post-trauma at follow-up was positively associated with severity of symptoms at baseline and with antidepressants treatment, and negatively associated with the number of children. Time since stillbirth was positively associated with the degree of improvement in posttraumatic symptoms only.ConclusionsOur findings suggest that mind-body group therapy may be associated with improvements in depression, post-traumatic stress symptoms, state anxiety, and suicidal ideation in women following stillbirth. Further research, including a control group is crucial for understanding of effective tools to treat this at-risk population.